A Preliminary Study: Marine Biogeography of Nautilus in the Bangka Belitung Seas, Indonesia - Siti Aisyah; Josaphat Tetuko Sri Sumantyo; Aditya Pamungkas; M Rizza Muftiadi; Muh Yusuf (Marine Science Department Diponegoro University, 2021)
Nautilus is the only surviving genus whose members were numerous and widely dispersed in the oceans throughout the Jurassic and Miocene times. It represents the only living member from the Family Nautilidae and is often considered as a living fossil. Nautilus is found with high biodiversity in Ambon, Indonesia, and were in special cases even found in Bangka Belitung, far from their original habitat. This study aimed to understand the historical component of the habitat and distribution of Nautilus in Bangka Belitung and to determine the depth, temperature, current, and environmental heterogeneity relate to Nautilus. Nautilus samples were found in Bangka Belitung Seas nearby a crack region at 50–75 m deep while the optimal depth of the Nautilus was 150–300 m, depending on the local area. The locations in the Bangka Belitung Seas where Nautilus found have sea surface temperatures between 30-31°C and 27-28°C during the East Monsoon and the West Monsoon respectivelly. The implications of temperature as a limiting factor are fairly significant, as it restricts the upper limit of the living habitat to predictable depths, which vary both geographically and seasonally during the West Monsoon when surface temperatures approach habitable levels. Sea currents at the Bangka Belitung Seas move at 0–0.6 m.s-1 during the East Monsoon and speed up near the North Natuna Sea. During the West Monsoon, currents predominantly flow from the Natuna Sea to the Java Sea at 0–0.5 m.s-1. Large-scale deep-water currents and the effects of smaller currents on scent dispersal influence the directional movements of Nautilus.